AI-Generated Transcripts for EFL Listening Monitoring, Regulation, and Reshaping Process Development - Cendikia Flory Aristia; Dellis Pratika; Niwayan Sukraini (DIDAKTIKA, 2026)
This qualitative case study investigates how 31 intermediate EFL learners used AI-generated transcripts to monitor, regulate, and reshape their listening comprehension during seven weeks of structured listening activities. Data from open-ended questionnaires and focus group discussions were analyzed thematically. The findings show that learners used transcripts as metacognitive scaffolds to compare spoken input with written text, identify misheard words and unfamiliar vocabulary, confirm interpretations, and revise misunderstandings. Rather than passively relying on transcripts, learners used them to verify unclear parts and reflect on comprehension gaps. Transcript use also helped learners shift from word-level decoding to a gist-oriented understanding by making unclear acoustic input more visible. The study suggests that guided use of AI transcripts can promote more reflective, strategic, and autonomous EFL listening.